2018
DOI: 10.1021/acsnano.7b08997
|View full text |Cite
|
Sign up to set email alerts
|

Elemental Identification by Combining Atomic Force Microscopy and Kelvin Probe Force Microscopy

Abstract: There are currently no experimental techniques that combine atomic-resolution imaging with elemental sensitivity and chemical fingerprinting on single molecules. The advent of using molecular-modified tips in noncontact atomic force microscopy (nc-AFM) has made it possible to image (planar) molecules with atomic resolution. However, the mechanisms responsible for elemental contrast with passivated tips are not fully understood. Here, we investigate elemental contrast by carrying out both nc-AFM and Kelvin prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 85 publications
(190 reference statements)
2
41
0
Order By: Relevance
“…In the related system of gr/Ir(111), nc-AFM measurements showed that, as a result, even within a single island, the corrugation of individual moiré unit cells varies smoothly by approximately ±8%, with occasional unit cells yielding even up to 20% larger corrugation [39]. Overall, our nc-AFM results are in agreement with the value obtained by Farwick zum Hagen et al from XSW (1.55 Å) [43], as well as with recent DFT results [42,43,53] and thus confirm that h-BN/Ir(111) belongs to the class of large-corrugation moiré systems.…”
Section: A Nc-afm Measurements On H-bn/ir(111)supporting
confidence: 92%
See 1 more Smart Citation
“…In the related system of gr/Ir(111), nc-AFM measurements showed that, as a result, even within a single island, the corrugation of individual moiré unit cells varies smoothly by approximately ±8%, with occasional unit cells yielding even up to 20% larger corrugation [39]. Overall, our nc-AFM results are in agreement with the value obtained by Farwick zum Hagen et al from XSW (1.55 Å) [43], as well as with recent DFT results [42,43,53] and thus confirm that h-BN/Ir(111) belongs to the class of large-corrugation moiré systems.…”
Section: A Nc-afm Measurements On H-bn/ir(111)supporting
confidence: 92%
“…[47]. nc-AFM measurements were carried out in a Createc LT-STM/AFM equipped with a qPlus tuning fork sensor [50] housed within the same UHV system at a temperature of 5 K. The attractive short-range interactions between the probe tip and the h-BN surface were minimized by passivating the tip apex by a carbon monoxide molecule (CO) [51][52][53].…”
Section: A Nc-afm Measurementsmentioning
confidence: 99%
“…However, Refs. [21,48] report that the properties, i.e., the electric field of CO tips, strongly depend on the tip backgrounds behind the terminating CO molecule. Hence, we conclude that the bond between the CO molecule and the metal tip is different for the various CO tips, although all these metal tips were terminated with a single metal atom prior to CO functionalization, leading to quantitatively different F z;SR ðz; 0Þ curves (see Fig.…”
mentioning
confidence: 99%
“…A major breakthrough in nc-AFM was the ability to resolve the internal structure of simple organic molecules in real space 2 , which was enabled by functionalizing a metallic AFM tip apex with a carbon-monoxide (CO) molecule. Since then, CO-terminated tips (CO tips) have been widely applied in AFM experiments to study molecular adsorbates [3][4][5][6][7][8][9] and various types of surfaces and adsorbates with atomic resolution [10][11][12][13][14][15] . The interaction of a CO tip with a sample surface is composed of different physical mechanisms, including van der Waals attraction and Pauli repulsion, which can be described by a Lennard-Jones potential 12,16,17 , and electrostatic interaction between the complex electric field of the CO tip and the sample electron density 12,13,18 .…”
mentioning
confidence: 99%